Auxiliary DO in Asian Englishes. Issue 4 (4th March 2021) - Schulz, Ninja
Abstract: To indicate emphasis, auxiliary do is used in affirmative contexts (do +) when no other auxiliary is present. It is thus rooted in the grammatical system of do‐support; however, do + does not always bear stress and can fulfil various discourse‐marking functions (Nevalainen & Rissanen, 1986). Positioned at the intersection of grammar and discourse, do + constitutes an interesting study for its use in 'non‐native' varieties of English since it can be assumed that the more salient grammatical functions are easier to master for learners. Focusing on Asian Englishes in contrast to Inner Circle varieties, this exploratory paper assesses the frequency and distribution of do + in the spoken and written parts of eight ICE components.